ORIENTATION TO MONEY OF AMBITIOUS PERSON - Barsukova, Oksana; V. Barsukova, Arina (Journal of process management and new technologies, 2021)
The article presents the results of an empirical study of orientation to money of ambitious person.Ambition and orientation to money arethemotivesofaperson’ssocialactivity. Ambition is a person’s desire to become a significant and recognized person for other people.Orientationtomoneyisa person’s a person’s desire to increase well-beingdesire to increase well-being. People who consider themselves ambitious have a low (75.75%) and an average (24.24%) orientation to money. People who do not consider themselves ambitious have a low (85.71%), average (7.14%) and high (7.14%) orientation to money.